Taiwanese Records of Oblong Large-Eye Seabream Gymnocranius oblongus (Teleostei: Lethrinidae) and Other Rare or Undetermined Large-Eye Seabreams - Chen, Wei-Jen; Ho, Hsuan-Ching; Borsa, Philippe (Frontiers in Marine Science, 2016)
The oblong large-eye seabream Gymnocranius oblongus Borsa, Béarez and Chen, 2010, has been described based on specimens from New Caledonia, the only locality where this species has been recorded up to now. Here, new records are reported from Taiwan, which is located over 7,000 km from the previously known site of occurrence. Nucleotide sequences at the cytochrome b locus of the Taiwanese samples of G. oblongus were provided and compared to those of the conspecific New Caledonian samples. The results showed little intraspecific DNA variation among the sequences (only three segregating sites along the 1140 -bp long aligned sequences). Further population genetic analysis revealed a relatively high level of genetic differentiation (Φst = 0.286) indicating limited gene flow between the two populations. The records thus available suggest a wide and antitropical distribution for this relatively rare and poorly known species. In addition to this finding, we report the first Taiwanese records of Gymnocranius satoi Borsa, Béarez, Paijo and Chen, 2013, a species widespread in the western Pacific, and of undetermined Gymnocranius specimens that potentially represent two new species.